2012
DOI: 10.1073/pnas.1117907109
|View full text |Cite
|
Sign up to set email alerts
|

Detailing the optimality of photosynthesis in cyanobacteria through systems biology analysis

Abstract: Photosynthesis has recently gained considerable attention for its potential role in the development of renewable energy sources. Optimizing photosynthetic organisms for biomass or biofuel production will therefore require a systems understanding of photosynthetic processes. We reconstructed a high-quality genome-scale metabolic network for Synechocystis sp. PCC6803 that describes key photosynthetic processes in mechanistic detail. We performed an exhaustive in silico analysis of the reconstructed photosyntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
323
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(342 citation statements)
references
References 40 publications
16
323
1
Order By: Relevance
“…2). An FBA analysis of photosynthetic cyanobacterial metabolism was recently used to explore some of these alternative pathways (Nogales et al, 2012). It was confirmed that NADPH/ATP rebalancing is required to match the energy demand of the metabolic system as a whole, not just the CalvinBenson cycle, and the importance of these alternative pathways increased with increasing light intensity.…”
Section: Energy Metabolism In Photosynthetic Tissuesmentioning
confidence: 99%
“…2). An FBA analysis of photosynthetic cyanobacterial metabolism was recently used to explore some of these alternative pathways (Nogales et al, 2012). It was confirmed that NADPH/ATP rebalancing is required to match the energy demand of the metabolic system as a whole, not just the CalvinBenson cycle, and the importance of these alternative pathways increased with increasing light intensity.…”
Section: Energy Metabolism In Photosynthetic Tissuesmentioning
confidence: 99%
“…To put the maximal turnover capacity of the LDHs in the cell extract into a quantitative perspective, it is relevant to realize that for Synechocystis to grow at max , i.e., with an 8-h doubling time, a minimal flux of carbon through the Calvin-Benson cycle of 3.70 mmol carbon/g DW/h is necessary (based on an estimated cellular composition of the biomass of C 4 H 7 O 2 N [29,35]). Hence, the measured in vitro enzyme activity of the lactate dehydrogenases demonstrates that in order to achieve the goal of a true "cell factory" for lactic acid (a cell that is able to channel the large majority of the fixed carbon into lactic acid), at least 10-fold-higher LDH activity is required than was achieved in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This translation results in a genome scale metabolic reconstruction, which represents a biochemical, genetic and genomic (BIGG) knowledge base [11] for a target organism. These reconstructions may then be used to investigate fundamental biological questions, guide industrial strain design, and provide a systems perspective for analysis of the expanding ocean of omics data [12][13][14].…”
Section: Systems Biologymentioning
confidence: 99%